2017
DOI: 10.1016/j.quaint.2015.06.065
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and subsistence at the Mesolithic and Bronze Age site of Aigyrzhal-2, Naryn valley, Kyrgyzstan

Abstract: River valleys in the Tien Shan Mountains of Kyrgyzstan have served as corridors for human dispersal since the Palaeolithic but little information exists on the history of human occupation in this remote and inaccessible region. Here, we report the results of a multidisciplinary study of Airgyrzhal-2, a high elevation (2005 m) site in the Naryn valley in central Kyrgyzstan. Two main occupation horizons were recognized, the earliest belonging to the Mesolithic (12th millennium cal. BC) and a later one dating fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Evidence of human occupancy during the Bronze Age is provided by archeological excavations at the closely nearby site Aigyrzhal-2 (2,005 m a.s.l.) in central Kyrgyzstan, ∼97 km northeast of Lake Chatyr Kol (Motuzaite Matuzeviciute et al, 2017). Domestic animal remains, such as horse and ovicaprines, and remains of cereals (grains and chaff), indicate that humans in the Tian Shan mountain valleys developed agricultural interests during this period (Motuzaite Matuzeviciute et al, 2017).…”
Section: Holocene Human and Mammal Presence In The Lake Chatyr Kol Camentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence of human occupancy during the Bronze Age is provided by archeological excavations at the closely nearby site Aigyrzhal-2 (2,005 m a.s.l.) in central Kyrgyzstan, ∼97 km northeast of Lake Chatyr Kol (Motuzaite Matuzeviciute et al, 2017). Domestic animal remains, such as horse and ovicaprines, and remains of cereals (grains and chaff), indicate that humans in the Tian Shan mountain valleys developed agricultural interests during this period (Motuzaite Matuzeviciute et al, 2017).…”
Section: Holocene Human and Mammal Presence In The Lake Chatyr Kol Camentioning
confidence: 99%
“…in central Kyrgyzstan, ∼97 km northeast of Lake Chatyr Kol (Motuzaite Matuzeviciute et al, 2017). Domestic animal remains, such as horse and ovicaprines, and remains of cereals (grains and chaff), indicate that humans in the Tian Shan mountain valleys developed agricultural interests during this period (Motuzaite Matuzeviciute et al, 2017). Yet, at the high-altitude site Lake Chatyr Kol pollen analysis did not indicate agricultural practice.…”
Section: Holocene Human and Mammal Presence In The Lake Chatyr Kol Camentioning
confidence: 99%
“…The free-threshing wheat grains correspond to compact wheat forms noted in the Dzhungar Mountains of Semirech’ye [6,18,19]. Furthermore, archaeobotanical research in Kyrgyzstan identified compact wheat forms at the sites of Uch Kurbu, Aigyrzhal-2, and Mol Bulak located in the highland regions (Fig 1c) [15,17], which suggests that compact wheat morphotypes are adapted to high elevations. Other researchers have also noted the suitability of compact wheats for agriculturalists in marginal environments of south and east Asia, such as monsoonal areas of India and the highlands of the Tibetan plateau [14,36].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of two types of free-threshing wheat rachis internodes (Fig 3) and the large diversity of wheat grain morphotypes found at Chap II and at other sites in Kyrgyzstan, such as Argyrzhal-2 and Uch-Kurbu [17], suggest that probably both tetraploid and hexaploid free-threshing wheat were cultivated. In China, archaeobotanical research mainly reports grain morphology, thus offering opportunities for future analysis of rachis internodes to test whether both tetraploid and hexaploid free-threshing wheats were cultivated there and, possibly, to resolve the timing and dispersal routes of these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation